Culturally and Linguistically Responsive Mathematics Instruction for English Learners in Multitiered Support Systems: PLUSS Enhancements - Sanford, Amanda K.; Pinkney, Christopher J.; Brown, Julie Esparza; Elliott, Cameron G.; Rotert, Emily N.; Sennott, Samuel C. (Learning disability quarterly, 2020)
This study examined the impact of linguistic and cultural enhancements to evidence-based mathematics instruction within a multitiered support system for English learners. The study employed a single subject changing criterion design for four fourth-grade students who were English learners with or at risk of a learning disability diagnosis in mathematics. Dual dependent variables were mathematics vocabulary acquisition and application in story problems. Student performance on identifying the correct mathematics vocabulary words when given the definition was measured across baseline and four phases of intervention. Students were also assessed on their ability to complete story problems that contained the target vocabulary. At each phase of the intervention, students showed an increase in performance on both vocabulary words correctly identified and story problems correctly completed. Implications for practice and future directions for research are discussed.